Synthesizing polypropylene with percolation network catalyzed by inorganic nanoparticles-functionalized Ziegler-Natta catalyst - Tingting Yang; Ao Li; Yawei Qin; Jin-Yong Dong (Polyolefins Journal, 2024)
Polypropylene is one of the most widely used synthetic resins, which is mainly synthesized with Ziegler-Natta catalysts. In this paper, the functionalized Ziegler-Natta catalyst is applied to prepare high-performance polypropylene. A new way to synthesize functionalized Ziegler-Natta catalysts is to dope with inorganic nanoparticles. The MgCl2/TiCl4/BMMF catalysts doped with halloysite nanotubes were prepared and applied to synthesize polypropylene containing less than 200ppm halloysite nanotubes. It is found that doping nanotubes in Ziegler-Natta catalyst has little impact on the structure, composition and activity of the catalyst, and polypropylene with high isotactic degree and molecular weight was synthesized with the functionalized Ziegler-Natta catalyst. Halloysite nanotubes are found to be dispersed in polypropylene in the form of individual nanotube, forming percolated network in the polymer melt effectively. Moreover, the polypropylene containing halloysite nanotubes exhibited better mechanical and thermal resistance properties as compared with conventional polypropylene, and the thermo-oxidative properties of which do not deteriorate as the introduction of nanotubes. This research provides a facile way to relieve the contradiction between the high activity of catalyst and high content of nanoparticles during the preparation of polyolefin nanocomposites by in-situ polymerization, and a new idea to prepare polyolefin nanocomposites by in-situ polymerization.